Ameliorative Effects of Component Chinese Medicine From Curcumae Rhizoma and Sparganii Rhizoma, a Traditional Herb Pair, on Uterine Leiomyoma in a Rat Model - Zhang, Li; Xu, Qiuxia; Li, Yao; Zhao, Hui; Shi, Xingming; Peng, Fu; Yu, Chenghao (Frontiers in Public Health, 2021)
Uterine leiomyoma (UL), common benign tumors in women of child-bearing age, are believed to be caused mainly by Qi stagnation and blood stasis, according to a theory of traditional Chinese medicine. Curcumae Rhizoma and Sparganii Rhizoma (CRSR) is a classical herb pair that activates blood circulation to dissipate blood stasis. The purpose of this study was to explore the prevention and treatment effects of CRSR component compatibility on UL in rats. We randomly assigned adult female non-pregnant rats into three groups: a normal control (NC) group, a UL model group, and a CRSR treatment group. We administered to the UL and CRSR groups oral gavage diethylstilbestrol and injected them with progesterone (P) to establish UL for 5 weeks. The CRSR group received a CRSR medicinal solution after daily modeling. The uterus morphology of the UL group showed significantly more swelling than did that of the NC group, and we found no significant abnormalities in the morphology of the CRSR group. The pathological changes associated with UL were relieved in the CRSR group. CRSR improved the related parameters of the uterus and ovarian coefficients, significantly reducing the concentrations of P in the serum and the concentrations of estradiol, P, estrogen receptor, and P receptor in the uterus and ovary. In addition, CRSR significantly improved the abnormal blood conditions of UL, shown by decreases in plasma viscosity, the erythrocyte sedimentation rate equation K value, and erythrocyte aggregation index. Therefore, CRSR component compatibility may prevent and cure UL through the above ways.